Beckman pH Monitor System - Dietrich, T. A. (1964)
This pH monitoring system was designed to operate in a weightless environment. It tests for proper fuel cell function and the potability of their water byproduct.
Keywords: Hydrogen-ion concentration--Measurement--Instruments; Scientific apparatus and instruments; Hydrogen-ion concentration; Beckman Instruments, Inc.